2010
DOI: 10.1017/s0022226710000010
|View full text |Cite
|
Sign up to set email alerts
|

Freezing effects and objects

Abstract: This paper is an investigation of freezing effects, that is, cases where an element (e.g. an object or a subject, or an element within it) is unable to move from a certain structural position. An account of the most prominent properties of freezing in Norwegian is followed by a comparative study of primarily English and Norwegian indirect objects, with important consequences for the general approach to indirect objects. Although recent analyses capture central properties of indirect objects, they fall short of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…This tension can also explain disparities in the acceptability of unaccusative subject islands reported in the literature. While we have not been able to find solid support for the more general freezing accounts of islands, we can offer new evidence in support of a more specialized, Caserelated conception of freezing as proposed by Lohndal (2011).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This tension can also explain disparities in the acceptability of unaccusative subject islands reported in the literature. While we have not been able to find solid support for the more general freezing accounts of islands, we can offer new evidence in support of a more specialized, Caserelated conception of freezing as proposed by Lohndal (2011).…”
Section: Discussionmentioning
confidence: 50%
“…Case-based conception of freezing (Lohndal 2011 Although one has to be cautious comparing experimental data across languages, English unaccusative subjects appear to be stronger islands than their Russian counterparts. We suggested that the English results could be accounted for by a combination of two principles: that extraction targets the base position of a constituent, and that Case movement induces freezing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most explicit early statement of the effect goes back to Wexler 1977 andCulicover 1980, with early Minimalist works such as Ormazabal, Uriagereka, andUribe-Etxebarria 1994 andTakahashi 1994 providing a new perspective on the effect. Many other works have argued for generalizations along the lines of (1), also providing empirical evidence for it; see Ross 1967:160, 1974, Postal 1972, Huybregts 1976, Diesing 1992, Freidin 1992, Collins 1994, Müller 1998, Lasnik 1999, Stepanov 2001, Rizzi 2006, Boeckx 2008, Gallego 2009, Lohndal 2011, Uriagereka 2012, and Corver 2014, among many others.…”
Section: Movement Out Of Moved Elementsmentioning
confidence: 94%
“…It has been observed that extraction out of moved syntactic objects is degraded; see, for instance, Ross (1967), Postal (1972), Wexler & Culicover (1980), Freidin (1992), Diesing (1992), Collins (1994), Müller (1998), Boeckx (2008), Gallego (2009), Lohndal (2011). Some definitions of freezing phenomena can be found in Ross (1967: 160, Frozen Structure Constraint), Wexler & Culicover (1980: 119, Freezing Principle), Diesing (1992: 128, Revised Extraction Constraint), Müller (1998: 22, Freezing).…”
Section: Freezing Effectsmentioning
confidence: 99%